Kinetics of Thermal Pyrolysis of High-Density Polyethylene - Abbas, Ammar S.; Saber, Marwa G. (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
Thermal pyrolysis kinetics of virgin high-density polyethylene (HDPE) was investigated. Thermal pyrolysis of HDPE was performed using a thermogravimetric analyzer in nitrogen atmosphere under non-isothermal conditions at different heating rates 4, 7, 10 °C/min. First-order decomposition reaction was assumed, and for the kinetic analysis Kissinger-Akahira-Sunose(KAS), Flynn-Wall-Ozawa(FWO) and Coats and Redfern(CR) method were used. The obtained values of average activation energy by the KAS and FWO methods were equal to137.43 and 141.52 kJ/mol respectively, these values were considered in good agreement, where the average activation energy value obtained by CR equation methods was slightly different which equal to 153.16 kJ/mol.